Hardness Variation of Welded Boron Steel Using Continuous Wave (CW) and Pulse Wave (PW) Mode of Fiber Laser - Khairul Ihsan, Yaakob; M., Ishak; Siti Rabiatull Aisha, Idris; Aiman, Mohd Halil; Nur Zalikha, Khalil (IOP Publishing, 2017)
Recent car manufacturer requirement in lightweight and optimum safety lead to utilization of boron steel with tailor welded blank approach. Laser welding process in tailor welded blank (TWB) production can be applied in continuous wave (CW) of pulse wave (PW) which produce different thermal experience in welded area. Instead of microstructure identification, hardness properties also can determine the behavior of weld area. In this paper, hardness variation of welded boron steel using PW and CW mode is investigated. Welding process is conducted using similar average power for both welding mode. Hardness variation across weld area is observed. The result shows similar hardness pattern across weld area for both welding mode. Hardness degradation at fusion zone (FZ) is due to ferrite formation existence from high heat input applied. With additional slower cooling rate for CW mode, the hardness degradation is become obvious. The normal variation of hardness behavior with PW mode might lead to good strength.